Metal-sulfur / selenium battery

By using targeted electrocatalysts as separator modification materials in metal-sulfur/selenium batteries, the problems of low conductivity and high reaction energy barrier of sulfur electrodes are solved, and the electrochemical performance and cycle stability of the battery are significantly improved, achieving the Highly efficient sulfur/selenium-based positive electrode conversion and capacity enhancement.

CN119230908APending Publication Date: 2024-12-31CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411487628.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The electrochemical properties of metal-sulfur/selenium batteries are limited by the low conductivity and high reaction energy barrier of sulfur electrodes, resulting in insufficient charge and discharge capacity and cycle stability, and the sulfur/selenide intermediate is easily dissolved, resulting in loss of active substances.

Method used

Targeted electrocatalysts, such as metal sulfides, metal nitrides, Prussian blue and their analogs and perovskite compounds, are used as functional membrane modification materials to reduce the speed-determining reaction energy barrier during the reaction process and promote sulfur. /Efficient conversion of selenium-based positive electrode.

Benefits of technology

It significantly improves the specific capacity, rate characteristics and cycle stability of metal-sulfur/selenium batteries, improves the electrochemical performance, and simplifies the preparation method of targeted electrocatalysts, and has good industrialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230908A_ABST
    Figure CN119230908A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemistry, and particularly relates to a metal-sulfur / selenium battery which comprises a positive electrode, a negative electrode, a diaphragm and electrolyte, an active material of the positive electrode is at least one of sulfur, selenium and a sulfur-selenium compound, and the negative electrode is a metal negative electrode; the positive electrode and / or the diaphragm are / is loaded with a targeted electrocatalyst, and the targeted electrocatalyst is one or more of metal sulfide, metal nitride, Prussian blue and analogues thereof, and a perovskite compound. The targeted electrocatalyst material is applied to the metal-sulfur / selenium battery to serve as a functional diaphragm modification material, so that the reaction energy barrier of the speed determining step in the reaction process can be directionally reduced, the reaction kinetics can be accelerated, the efficient conversion of a sulfur / selenium-based positive electrode can be promoted, and the electrochemical performance of the metal-sulfur / selenium battery can be remarkably improved. In addition, the preparation method of the targeted electrocatalyst material is simple and easy to obtain, and the technology has good industrialization potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry, and in particular relates to a metal-sulfur / selenium battery. Background Art

[0002] Developing advanced electrochemical energy storage technology and developing efficient electrochemical energy storage systems are key to accelerating the construction of a green, low-carbon, circular development economic system. The limited specific capacity of commercial lithium-ion battery cathode materials (ternary, lithium iron phosphate) makes it difficult for the energy density of lithium-ion batteries to exceed 500Whkg. -1 , becoming an important factor restricting the further development of lithium-ion batteries. In order to meet the growing demand for high specific energy density energy storage devices, elemental sulfur (selenium) has attracted widespread attention due to its high theoretical specific capacity and abundant reserves. In particular, lithium-sulfur (selenium) batteries have a theoretical energy density of 2567Wh kg -1 and 1160Wh kg -1 In addition to the lithium-sulfur (selenium) battery system, sodium / potassium-sulfur (selenium) batteries and magnesium / aluminum-sulfur (selenium) batteries based on sodium and potassium, which are abundant and have similar physical and chemical properties to metallic lithium, and magnesium and aluminum, which are low-cost and highly safe multivalent metals, have also become battery systems with great research value and development potential.

[0003] In fact, although the sulfur (selenium) electrode has an outstanding theoretical specific capacity, the electrochemical performance of metal-sulfur (selenium) batteries still has some bottlenecks. The biggest advantage of the sulfur electrode is its high theoretical specific capacity, but its low conductivity (5×10 -28 Sm -1 ) limits the battery's charge and discharge capacity at high rates. In addition, sulfur reduction and sulfur conversion reactions involve multi-electron transfer processes. The high reaction energy barrier of the rate-determining step leads to slow reaction kinetics, limiting the complete conversion of sulfur. Although the theoretical capacity of the selenium electrode is lower than that of the sulfur electrode, its conductivity (1×10 -3 S m -1 ) is much higher than sulfur, and due to its higher density (4.81 gcm -3 ) makes its theoretical volume capacity comparable to that of sulfur.

[0004] In the metal-sulfur (selenium) battery system, sulfur (selenium) and polysulfide / polyselenide intermediates involved in the reaction process are easily dissolved in the electrolyte, resulting in the loss of active substances and rapid capacity decay. At the same time, the intermediate reactants that shuttle to the negative electrode side will corrode the metal surface. The introduction of electrocatalysts can promote the reaction kinetics, but if the electrocatalysts are not targeted, it is difficult to fundamentally overcome the problem of high reaction energy barriers in the rate-determining step of sulfur (selenium) conversion. In addition, blindly accelerating the reaction rate may increase the formation of polysulfides. If these intermediates are difficult to further convert in the rate-determining step due to the high reaction energy barrier, the "shuttle effect" will be aggravated, which is counterproductive to the improvement of electrochemical performance. Therefore, for the rate-determining step with a high energy barrier in the reaction process, it is very important to find and design suitable targeted electrocatalysts to effectively inhibit the dissolution-shuttle behavior of intermediates in the conversion process and directionally reduce the reaction energy barrier of the rate-determining step to improve the key electrochemical properties of metal-sulfur (selenium) batteries, such as specific capacity, rate characteristics, and cycle stability. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a metal-sulfur / selenium battery. The present invention utilizes the directional electrocatalytic effect of a targeted catalyst on the rate-determining step in the reaction process to improve the electrochemical performance of the metal-sulfur / selenium battery.

[0006] The present invention provides a metal-sulfur / selenium battery, comprising: a positive electrode, a negative electrode, a separator and an electrolyte; the active material of the positive electrode is at least one of sulfur, selenium and a sulfur-selenium compound, and the negative electrode is a metal negative electrode; the positive electrode and / or the separator are loaded with a targeted electrocatalyst, and the targeted electrocatalyst is one or more of metal sulfides, metal nitrides, Prussian blue and its analogs and perovskite compounds.

[0007] Preferably, the metal sulfide is one or more of MoS2, WS2, SnS and Bi2S3; the metal nitride is TiN and / or Ni3N.

[0008] Preferably, the active material of the positive electrode is a supported active material, including a porous carrier and one of sulfur, selenium and a sulfur-selenium compound supported on the porous carrier.

[0009] Preferably, the metal negative electrode is one of lithium, sodium, potassium, magnesium and aluminum.

[0010] Preferably, the electrolyte is a carbonate-based electrolyte, an ether-based electrolyte or an ionic liquid.

[0011] Preferably, the diaphragm is a glass fiber membrane.

[0012] Preferably, the positive electrode loaded with the targeted electrocatalyst is prepared by mixing a positive electrode active material, a targeted electrocatalyst, a conductive agent, a binder and a solvent.

[0013] Preferably, the diaphragm loaded with the targeted electrocatalyst is prepared according to the following steps:

[0014] mixing a targeted electrocatalyst, a conductive agent, a binder and a solvent to obtain a slurry;

[0015] The slurry is coated on the surface of the diaphragm and dried to obtain a diaphragm modified with a targeted electrocatalyst.

[0016] Preferably, the mass ratio of the targeted electrocatalyst, the conductive agent and the binder is (5-10):(0.5-5):1.

[0017] Preferably, the slurry has a dry coating thickness of 50 to 500 μm.

[0018] Compared with the prior art, the present invention provides a metal-sulfur / selenium battery, comprising: a positive electrode, a negative electrode, a diaphragm and an electrolyte; the active material of the positive electrode is at least one of sulfur, selenium and sulfur-selenium compounds, and the negative electrode is a metal negative electrode; the positive electrode and / or the diaphragm are loaded with a targeted electrocatalyst, and the targeted electrocatalyst is one or more of metal sulfides, metal nitrides, Prussian blue and its analogs and perovskite compounds. The present invention applies targeted electrocatalyst materials to metal-sulfur / selenium batteries as functional diaphragm modification materials, which can directionally reduce the reaction energy barrier of the rate-determining step in the reaction process, accelerate the reaction kinetics, promote the efficient conversion of sulfur / selenium-based positive electrodes, and significantly improve the electrochemical performance of metal-sulfur / selenium batteries. In addition, the preparation method of the targeted electrocatalyst material used in the present invention is simple and easy to obtain, and the technology has good industrialization potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0020] Figure 1 is a SEM image of the selenium disulfide-porous carbon composite material provided in Example 1 of the present invention;

[0021] Figure 2 is a cyclic voltammetry curve of a potassium-selenium disulfide battery assembled using a common diaphragm and a TiN-modified diaphragm provided in Example 1 of the present invention;

[0022] Figure 3 This is a graph showing the cycle performance test results of a potassium-selenium disulfide battery assembled using a common diaphragm and a TiN-modified diaphragm provided in Example 1 of the present invention;

[0023] Figure 4 is a SEM image of Bi2S3 provided in Example 2 of the present invention;

[0024] Figure 5 1 is a cyclic voltammetry curve of a potassium-sulfur battery using a common diaphragm and a Bi2S3 modified diaphragm provided in Example 2 of the present invention;

[0025] Figure 6 This is a graph showing the rate test results of a potassium-sulfur battery using a common diaphragm and a Bi2S3 modified diaphragm provided in Example 2 of the present invention;

[0026] Figure 7 1 is a graph showing the cycle performance test results of a potassium-sulfur battery using a common diaphragm and a Bi2S3 modified diaphragm provided in Example 2 of the present invention;

[0027] Figure 8 3 is a charge and discharge curve diagram of a lithium-sulfur battery using a common separator and a PB-modified separator provided in Example 3 of the present invention;

[0028] Fig. 9 It is a charge and discharge curve diagram of the Se-CNT positive electrode and the Se-CNT+SrLNO positive electrode provided in Example 4 of the present invention for aluminum-selenium battery;

[0029] Fig.10 This is a graph showing the cycle performance test results of the Se-CNT positive electrode and Se-CNT+SrLNO positive electrode provided in Example 4 of the present invention for aluminum-selenium batteries. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention provides a metal-sulfur / selenium battery, comprising: a positive electrode, a negative electrode, a separator and an electrolyte; the active material of the positive electrode is at least one of sulfur, selenium and a sulfur-selenium compound, and the negative electrode is a metal negative electrode; the positive electrode and / or the separator are loaded with a targeted electrocatalyst, and the targeted electrocatalyst is one or more of metal sulfides, metal nitrides, Prussian blue and its analogs and perovskite compounds.

[0032] In the battery provided by the present invention, in the targeted electrocatalyst, the metal sulfide is preferably one or more of MoS2, WS2, SnS and Bi2S3. In the present invention, the specific preparation process of the metal sulfide preferably includes: dissolving a metal salt in a solvent, adding a certain amount of a sulfur source and stirring, then performing a solvothermal reaction, and finally collecting the product by centrifugation, washing, and drying; wherein the metal salt is preferably at least one of sodium molybdate, tungsten chloride, tin chloride, and bismuth nitrate; the sulfur source is preferably at least one of sulfur powder, thiourea, and N-phenylthiourea; the temperature of the solvothermal reaction is preferably 100 to 180°C, specifically 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or 180°C; the time of the solvothermal reaction is preferably 10 to 24h, specifically 10h, 12h, 14h, 16h, 18h, 20h, 22h, or 24h; the solvent is preferably any one of ethanol, ethylene glycol, and N,N-dimethylformamide (DMF).

[0033] In the battery provided by the present invention, in the targeted electrocatalyst, the metal nitride is preferably TiN and / or Ni3N. In the present invention, the specific preparation process of the metal nitride preferably includes: mixing a metal inorganic salt and polyvinyl pyrrolidone in a solvent, adding an aqueous sodium persulfate solution, and annealing the collected precursor under an ammonia atmosphere to obtain a product; wherein the metal inorganic salt preferably includes any one of titanium chloride, nickel chloride, ammonium titanate and nickel nitrate; the solvent preferably includes any one of ethanol, water and DMF; the temperature of the annealing treatment is preferably 300-600°C, specifically 300°C, 400°C, 500°C or 600°C; the time of the annealing treatment is preferably 3-6h, specifically 3h, 4h, 5h or 6h.

[0034] In the battery provided by the present invention, in the targeted electrocatalyst, the specific preparation process of the Prussian blue and its analogues preferably includes: dissolving K4Fe(CN)6·3H2O and sodium citrate in water, dripping a metal salt aqueous solution thereto, centrifuging and washing to collect a solid sample after aging, and then vacuum drying to obtain a product; wherein the metal salt preferably includes any one of nickel chloride, manganese chloride, ferric chloride, ferric sulfate and cobalt chloride; the aging time is preferably 6 to 24 hours, specifically 6 hours, 12 hours, 18 hours or 24 hours; the drying temperature is preferably 60 to 100°C, specifically 60°C, 70°C, 80°C, 90°C or 100°C; the drying time is preferably 6 to 24 hours, specifically 6 hours, 12 hours, 18 hours or 24 hours.

[0035] In the battery provided by the present invention, in the targeted electrocatalyst, the specific preparation process of the perovskite compound preferably includes: dissolving the metal salt in water, then adding ethylenediaminetetraacetic acid and citric acid, adding ammonia water to adjust the pH value of the solution to neutral, then placing it in a water bath and stirring until the solution evaporates into a gel, then heat treating to obtain a fluffy precursor powder, and then calcining in air to obtain the product; wherein the metal salt preferably includes any of strontium nitrate, nickel nitrate, calcium nitrate, cerium nitrate, lanthanum nitrate and barium nitrate; the temperature of the water bath is preferably 60 to 100°C, specifically 60 ℃, 70℃, 80℃, 90℃ or 100℃; the heat treatment temperature is preferably 170-250℃, specifically 170℃, 190℃, 200℃, 220℃ or 250℃; the heat treatment time is preferably 6-12h, specifically 6h, 8h, 10h or 12h; the calcination temperature is preferably 600-1200℃, specifically 600, 700, 800, 900, 1000, 1100 or 1200; the calcination time is preferably 1-5h, specifically 1h, 2h, 3h, 4h or 5h.

[0036] In the battery provided by the present invention, in the positive electrode, the active material of the positive electrode is preferably a supported active material, that is, in addition to at least one of sulfur, selenium and sulfur-selenium compounds as an active ingredient, it also includes a porous carrier; the content of the active ingredient in the supported active material is preferably 30-70wt%, specifically 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt% or 70wt%; the porous carrier is preferably a porous carbon-based carrier, including but not limited to commercial carbon nanotubes, porous carbon prepared by salt crystal template-assisted method or MOF-derived porous carbon material.

[0037] In the battery provided by the present invention, in the positive electrode, the specific process of preparing porous carbon by the salt crystal template-assisted method preferably includes: mixing the salt crystal template and the carbon source evenly in a certain proportion, calcining the precursor under an inert atmosphere, and then removing residual inorganic matter by water washing, and obtaining the corresponding porous carbon material after drying. Wherein, the salt crystal template includes but is not limited to one or more of NaHCO3, K2CO3 and NaCl; the carbon source includes but is not limited to one or more of cellulose, methyl cellulose and carboxymethyl cellulose, and the mass ratio of the salt crystal template to the carbon source is preferably (1-10):1, specifically 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1; the inert atmosphere is preferably argon or nitrogen; the calcination temperature is preferably 700-1000°C, specifically 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C; the drying temperature is preferably 60-100°C, specifically 60°C, 70°C, 80°C, 90°C or 100°C; the drying time is preferably 6-24h, specifically 6h, 12h, 18h or 24h.

[0038] In the battery provided by the present invention, in the positive electrode, the MOF-derived porous carbon material is preferably ZIF-8-derived porous carbon or ZIF-67-derived porous carbon. The specific preparation process of the MOF-derived porous carbon material preferably includes: dissolving a zinc source or a cobalt source and 2-methylimidazole in a solvent, respectively, quickly mixing the two solutions, and then centrifuging, washing with methanol, and drying to obtain a precursor; calcining the precursor under an inert atmosphere, and then acid etching, washing with water, and drying to obtain the final porous carbon material. wherein the zinc source is preferably at least one of zinc acetate, zinc chloride and zinc nitrate; the cobalt source is preferably at least one of cobalt acetate and cobalt nitrate; the solvent is preferably water or methanol; the temperature of the rapid mixing is preferably 10-40°C, specifically 10°C, 15°C, 20°C, 25°C (room temperature), 30°C, 35°C or 40°C; the time of the rapid mixing is preferably 24-72h, specifically 24h, 36h, 48h, 60h or 72h; the inert atmosphere is preferably nitrogen; the calcination temperature is preferably 300-1000°C, specifically 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, and the calcination time is preferably 2-8h, specifically 2h, 3h, 4h, 5h, 6h, 7h or 8h.

[0039] In the battery provided by the present invention, in the positive electrode, the active ingredient of the supported active material (at least one of sulfur, selenium and sulfur-selenium compounds) is preferably supported on the porous carrier by a melt-diffusion method; wherein the mass ratio of the active ingredient to the porous carrier is preferably (1-3):1, specifically 1:1, 1.5:1, 2:1, 2.5:1 or 3:1; the melting temperature is preferably 140-300°C, specifically 155°C, 260°C or 266°C; the loading time is preferably 24-72h, specifically 24h, 36h, 48h, 60h or 72h.

[0040] In the battery provided by the present invention, in the positive electrode, the positive electrode not loaded with the targeted electrocatalyst is prepared by mixing a positive electrode active material, a conductive agent, a binder and a solvent. Wherein, the positive electrode active material is preferably a loaded active material; the conductive agent includes but is not limited to conductive carbon black; the binder includes but is not limited to polyvinylidene fluoride (PVDF); the solvent includes but is not limited to N-methylpyrrolidone (NMP); the mass ratio of the positive electrode active material, the conductive agent and the binder is preferably (5-10): (1-3): 1, wherein the mass ratio of the positive electrode active material and the binder can be specifically 5: 1, 6: 1, 7: 1, 8: 1, 9: 1 or 10: 1, and the mass ratio of the conductive agent and the binder can be specifically 1: 1, 1.5: 1, 2: 1, 2.5: 1 or 3: 1.

[0041] In the battery provided by the present invention, in the positive electrode, the positive electrode loaded with the targeted electrocatalyst is prepared by mixing a positive electrode active material, a targeted electrocatalyst, a conductive agent, a binder and a solvent. Wherein, the positive electrode active material is preferably a supported active material; the conductive agent includes but is not limited to conductive carbon black; the binder includes but is not limited to polyvinylidene fluoride (PVDF); the solvent includes but is not limited to N-methylpyrrolidone (NMP); the mass ratio of the positive electrode active material, the targeted electrocatalyst, the conductive agent and the binder is preferably (4-8): (0.5-2): (1-3): 1, wherein the mass ratio of the positive electrode active material and the binder can be specifically 4: 1, 5: 1, 6: 1, 7: 1 or 8: 1, the mass ratio of the targeted electrocatalyst and the binder can be specifically 0.5: 1, 1: 1, 1.5: 1 or 2: 1, and the mass ratio of the conductive agent and the binder can be specifically 1: 1, 1.5: 1, 2: 1, 2.5: 1 or 3: 1.

[0042] In the battery provided by the present invention, in the diaphragm, the base membrane of the diaphragm is preferably a glass fiber membrane; the diaphragm can be either a diaphragm not loaded with the targeted electrocatalyst or a diaphragm loaded with the targeted electrocatalyst.

[0043] In the battery provided by the present invention, in the diaphragm, the diaphragm loaded with the targeted electrocatalyst is preferably prepared according to the following steps: mixing the targeted electrocatalyst, the conductive agent, the binder and the solvent to obtain a slurry; applying the slurry to the surface of the diaphragm, drying, and obtaining a diaphragm modified with the targeted electrocatalyst. In the above-mentioned preparation steps provided by the present invention, the conductive agent includes but is not limited to carboxylated carbon nanotubes; the binder includes but is not limited to polyvinylidene fluoride (PVDF); the solvent includes but is not limited to N-methylpyrrolidone (NMP); the mass ratio of the targeted electrocatalyst, the conductive agent and the binder is preferably (5-10): (0.5-5): 1, wherein the mass ratio of the targeted electrocatalyst to the binder can be specifically 5: 1, 6: 1, 7: 1, 8: 1, 9: 1 or 10: 1, and the mass ratio of the conductive agent to the binder can be specifically 0. 5:1, 1:1, 2:1, 3:1, 4:1 or 5:1; the drying temperature is preferably 60-100°C, specifically 60°C, 70°C, 80°C, 90°C or 100°C; the drying time is preferably 6-24h, specifically 6h, 12h, 18h or 24h; the coating dry thickness of the slurry is preferably 50-500μm, specifically 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, 350μm, 400μm, 450μm or 500μm.

[0044] In the battery provided by the present invention, the metal negative electrode is preferably one or more of lithium, sodium, potassium, magnesium and aluminum.

[0045] In the battery provided by the present invention, the electrolyte is preferably a carbonate-based electrolyte, an ether-based electrolyte or an ionic liquid.

[0046] The technical solution provided by the present invention applies the targeted electrocatalyst material to the metal-sulfur / selenium battery as a functional diaphragm modification material, which can directionally reduce the reaction energy barrier of the rate-determining step in the reaction process, accelerate the reaction kinetics, promote the efficient conversion of the sulfur / selenium-based positive electrode, and significantly improve the electrochemical performance of the metal-sulfur / selenium battery. In addition, the preparation method of the targeted electrocatalyst material used in the present invention is simple and easy to obtain, and the technology has good industrialization potential.

[0047] The experimental results show that the application of targeted electrocatalyst materials in metal-sulfur / selenium batteries can significantly improve the electrochemical performance of the batteries. The capacity of the potassium-selenium disulfide battery system is as high as 663 mAh g -1 The potassium-sulfur battery system has a capacity of up to 988 mAh g -1 The capacity of the lithium-sulfur system is as high as 871 mAh g -1 The capacity of aluminum-selenium battery system is as high as 1082mAh·g -1 .

[0048] For the purpose of greater clarity, the invention is described in detail through the following examples.

[0049] Example 1

[0050] Preparation of porous carbon materials by salt crystal template method: 5 g NaHCO3 and 1 g methyl cellulose were thoroughly mixed and placed in a crucible under argon atmosphere at 5 °C min -1 The temperature was raised to 200°C at a heating rate and maintained for 2 h, and then further raised to 800°C for carbonization. After the temperature was completely lowered, the product was taken out, washed thoroughly with water to remove the template, and then placed in an oven for drying.

[0051] Loading selenium disulfide: The obtained porous carbon material was mixed with selenium disulfide in a mass ratio of 1:2 and poured into a glass tube for vacuum packaging. -1 The temperature was raised to 260° C. at a heating rate of 100° C. and maintained for 48 h, and then treated at 300° C. for 30 min to remove excess selenium disulfide components to obtain a selenium disulfide-porous carbon composite material (the selenium disulfide content was about 50 wt%).

[0052] The selenium disulfide-porous carbon composite material prepared in this example was observed by scanning electron microscope (SEM), and the results are as follows: Figure 1 As shown, Figure 1 This is a SEM image of the selenium disulfide-porous carbon composite material provided in Example 1 of the present invention. Figure 1 It can be seen that selenium disulfide is evenly distributed in the porous carbon, and the rich pore structure facilitates the transmission of ions / electrons.

[0053] Preparation of selenium disulfide-porous carbon positive electrode: The obtained selenium disulfide-porous carbon composite material is evenly mixed with conductive carbon black and PVDF in a mass ratio of 7:2:1, the mixture is dispersed in N-methylpyrrolidone, and a uniform slurry is obtained after sufficient stirring. The slurry is drop-coated on a stainless steel gasket, and vacuum dried at 80°C for 12 hours to obtain a positive electrode sheet.

[0054] In this embodiment, commercial nano-scale titanium nitride is used as a targeted electrocatalyst material to modify a battery separator to improve the electrochemical performance of a potassium-selenium disulfide battery.

[0055] Preparation of titanium nitride modified membrane: The titanium nitride is uniformly mixed with carboxylated carbon nanotubes and PVDF in a mass ratio of 6:3:1, wherein the mass of titanium nitride is 600 mg; the mixture is poured into a weighing bottle, 10 mL of NMP is added, and stirred for 12 hours, and then the resulting slurry is uniformly coated on a glass fiber membrane with a coating thickness of 200 μm, and vacuum dried at 80°C for 12 hours to obtain a membrane with a coating dry thickness of 200 μm; the membrane is punched into a disc with a diameter of 19 mm as a functional modified membrane.

[0056] The button cell was assembled with the selenium disulfide-porous carbon positive electrode, TiN-modified separator and potassium metal negative electrode, and the electrolyte was 1.0M KFSI / EC-DEC. Then, the electrical performance of the battery was tested in the voltage range of 0.5-2.8V (vs.K + / K), set up a battery with ordinary glass fiber separator as a comparison, the test results are as follows Figures 2-3 As shown:

[0057] Figure 2 1 is a cyclic voltammetry curve of a potassium-selenium disulfide battery assembled using a common diaphragm and a TiN modified diaphragm provided in Example 1 of the present invention. Figure 2 As shown in the figure, the redox peak current of the cyclic voltammetry curve of the potassium-selenium disulfide battery using TiN modified diaphragm is higher, and the voltage polarization of the redox reaction is also smaller. In particular, the potassium-selenium disulfide battery using TiN modified diaphragm shows a reduction peak at a low potential, which corresponds to the high energy barrier reaction step of generating the final products K2S and K2Se. The right-shifted reduction potential (0.7V) and the higher peak current reflect the efficient and directional electrocatalytic effect of TiN on the potassium storage reaction process of selenium disulfide.

[0058] Figure 3 1 is a graph showing the cycle performance test results of a potassium-selenium disulfide battery assembled using a common diaphragm and a TiN modified diaphragm provided in Example 1 of the present invention. Figure 3 As shown in the figure, the battery using TiN modified separator in Example 1 exhibits higher capacity and better cycle stability than the battery using ordinary separator. The battery capacity using TiN modified separator is almost twice that of the battery using ordinary separator, which is due to the fact that TiN can directionally reduce the high reaction energy barrier in the potassium-selenium disulfide battery reaction process and improve the conversion of selenium disulfide. -1 At the current density, the capacity is as high as 663mAh g -1 After 50 cycles, the battery with TiN modified separator can retain 490 mAh g -1 Therefore, the TiN modified diaphragm prepared in Example 1 as a diaphragm of a potassium-selenium disulfide battery has a targeted electrocatalytic effect on the conversion of selenium disulfide, and can effectively improve the potassium storage capacity and cycle stability of selenium disulfide.

[0059] Example 2

[0060] Preparation of ZIF-8 derived porous carbon: 9.0 g of 2-methylimidazole was dissolved in 50 mL of water, which was recorded as solution I; 2.5 g of Zn(CH3COO)2·2H2O was dissolved in 50 mL of water, which was recorded as solution II; solution II was quickly poured into solution I and stirred at room temperature for 48 h. The reaction product was centrifuged, washed with methanol three times, and then dried in an oven at 80°C to obtain ZIF-8; the obtained ZIF-8 was kept at 400°C for 2 h and then kept at 800°C for 2 h, with a heating rate of 2°C·min -1 , and then the carbonized product was acid-washed with 2M HCl solution, and finally washed with water and dried to obtain ZIF-8-derived porous carbon.

[0061] Sulfur loading: The obtained ZIF-8 derived porous carbon and high purity sulfur were mixed in a mass ratio of 1:2 and poured into a glass tube for vacuum packaging. -1 The temperature was raised to 155° C. at a heating rate of 1000 ° C. and kept at this temperature for 48 h, and then treated at 200° C. for 30 min to remove excess sulfur components to obtain a sulfur-porous carbon composite material (the sulfur content is about 50 wt%).

[0062] Preparation of sulfur-porous carbon positive electrode: The obtained sulfur-porous carbon composite material is mixed with conductive carbon black and PVDF in a mass ratio of 7:2:1 to prepare an electrode.

[0063] In this embodiment, bismuth sulfide is used as a targeted electrocatalyst material to modify a battery separator to improve the electrochemical performance of a potassium-sulfur battery.

[0064] Preparation of bismuth sulfide: Bi(NO3)3·5H2O and thiourea were added to 80 mL of ethylene glycol solvent in a molar ratio of 1:5, stirred for 30 min, and then subjected to solvothermal reaction at 180°C; then centrifuged, washed with water 5 times, and dried to collect the Bi2S3 sample.

[0065] The Bi2S3 prepared in this example was observed by scanning electron microscope (SEM), and the results are as follows: Figure 4 As shown, Figure 4 This is a SEM image of Bi2S3 provided in Example 2 of the present invention. Figure 4 It can be seen that the Bi2S3 prepared in this example has a rod-like morphology.

[0066] Preparation of bismuth sulfide modified diaphragm: Prepare Bi2S3 modified diaphragm according to the diaphragm preparation method of Example 1.

[0067] The above-obtained sulfur-porous carbon composite positive electrode, Bi2S3 modified separator and metallic potassium negative electrode were assembled into a potassium-sulfur battery, and the electrolyte was 0.8M KPF6 / EC-DEC. Subsequently, the electrical performance of the battery was tested in the test voltage range of 0.5-3.0V (vs.K + / K), set up a battery with ordinary glass fiber separator as a comparison, the test results are as follows Figures 5 to 7 As shown:

[0068] Figure 5 1 is a cyclic voltammetry curve of a potassium-sulfur battery using a common diaphragm and a Bi2S3 modified diaphragm provided in Example 2 of the present invention. Figure 5 It can be seen that the Bi2S3-modified diaphragm significantly increases the response current during the sulfur redox reaction, especially the reduction voltage corresponding to the high reaction energy barrier step (K2S3→K2S) at low potential increases. Secondly, the oxidation voltage also decreases during the charging process, indicating that the polarization voltage is reduced, reflecting that Bi2S3 has a directional promoting effect on the sulfur redox reaction process.

[0069] Figure 6 This is a graph showing the rate test results of a potassium-sulfur battery using a common diaphragm and a Bi2S3 modified diaphragm provided in Example 2 of the present invention. Figure 6 It can be seen that the battery using ordinary separators shows poor rate performance. When the charge and discharge rate is 1.0C, the battery has almost no capacity. After the separator is modified with Bi2S3, the rate performance of the battery is improved.

[0070] Figure 7 This is a graph showing the cycle performance test results of a potassium-sulfur battery using a common diaphragm and a Bi2S3 modified diaphragm provided in Example 2 of the present invention. Figure 7 It can be seen that after 150 cycles at 1.0C, the remaining capacity of the battery using the ordinary separator is only 280 mAh g -1 , while the potassium-sulfur battery using Bi2S3 modified separator can retain 988mAh g -1 capacity.

[0071] Example 3

[0072] Sulfur loading: Commercial carbon nanotubes were used as carriers and sulfur was loaded according to the method described in Example 2 to obtain a sulfur-carbon nanotube electrode.

[0073] Preparation of sulfur-carbon nanotube positive electrode: The obtained sulfur-carbon nanotube electrode is mixed with conductive carbon black and PVDF in a mass ratio of 7:2:1 to prepare an electrode.

[0074] In this embodiment, Prussian blue (PB) is used as a targeted electrocatalyst material to modify a battery separator to improve the electrochemical performance of a lithium-sulfur battery.

[0075] Preparation process of Prussian blue PB: 4 mmol of NaFe(CN)·10H2O and 29 mmol of sodium citrate were dissolved in 100 mL of deionized water, marked as solution A; similarly, 6 mmol of FeSO4·7H2O was dissolved in 100 mL of deionized water, marked as solution B; after each solution was stirred for 1 hour, solution B was dripped into solution A at a drip rate of 1 mL / min with the help of a peristaltic pump; then, the mixture was allowed to stand for 12 hours; the precipitate was obtained by centrifugation, during which it was rinsed several times with deionized water and ethanol; finally, the wet precipitate was placed in a vacuum oven and baked at 80°C for 12 hours to obtain PB.

[0076] Preparation of PB modified membrane: A Prussian blue PB modified membrane was prepared according to the membrane preparation method of Example 1.

[0077] The above-obtained sulfur-carbon nanotube positive electrode, PB modified separator and metal lithium negative electrode were assembled into a button cell, and the electrolyte was 1.0M LiTFSI / DME-DOL. Subsequently, the electrical performance of the battery was tested, and the test voltage range was 1.7-2.8V (vs.Li + / Li), and set up a battery with ordinary glass fiber separator as a comparison. The test results are as follows Figure 8 As shown:

[0078] Figure 8 3 is a charge and discharge curve diagram of a lithium-sulfur battery using a common separator and a PB-modified separator provided in Example 3 of the present invention. Figure 8 It can be seen that the charge and discharge capacity of the battery is improved by using PB modified diaphragm, and the discharge capacity can reach 871mAh g at 1C. -1 , the reaction polarization voltage also decreased significantly, indicating that the prepared Prussian blue PB exhibited obvious electrocatalytic effect in lithium-sulfur batteries.

[0079] Example 4

[0080] Sulfur loading: Commercial carbon nanotubes were used as carriers. Carbon nanotubes and selenium were mixed in a mass ratio of 1:2 and poured into a glass tube for vacuum packaging. -1 The temperature was raised to 266° C. at a heating rate of 100° C. and kept at this temperature for 48 h, and then treated at 300° C. for 30 min to remove excess selenium components to obtain a selenium-carbon nanotube composite material (with a selenium content of about 50 wt%).

[0081] In this embodiment, the perovskite compound SrLaNiO3 is used as a targeted electrocatalyst material to modify the positive electrode of the battery to improve the electrochemical performance of the aluminum-selenium battery.

[0082] Preparation of perovskite compound SrLaNiO3: Dissolve citric acid and ethylenediaminetetraacetic acid in water, add nickel nitrate, lanthanum nitrate and strontium nitrate and stir evenly, wherein the mass ratio of citric acid, ethylenediaminetetraacetic acid and metal salt is 2:1:1, add ammonia water to adjust the pH value of the mixed solution to neutral, and then continue to stir the mixed solution in an 80°C water bath until a gel is formed, and then heat it at 220°C for 8h and then calcine it at 800°C for 3h, and finally collect the SrLaNiO3 sample.

[0083] Preparation of sulfur-carbon nanotube-SrLNO positive electrode: The selenium-carbon nanotube composite material, the perovskite compound SrLaNiO3, the conductive agent and the binder are prepared in a mass ratio of 6:1:2:1.

[0084] The sulfur-carbon nanotube-SrLNO positive electrode obtained above and the metal aluminum negative electrode were assembled into a Swaglok type battery, and the electrolyte used the ionic liquid AlCl3 / Et3NHCl=1.5:1 (molar ratio); then, the electrical performance of the battery was tested, and the test voltage range was 0.1~2.3V (vs.Al + / Al), and set up a battery using sulfur-carbon nanotube positive electrode (that is, no perovskite compound SrLaNiO3 was added when preparing the positive electrode) as a comparison. The test results are as follows Figures 9-10 As shown:

[0085] Fig. 9 4 is a charge and discharge curve diagram of the Se-CNT positive electrode and the Se-CNT+SrLNO positive electrode provided in Example 4 of the present invention for an aluminum-selenium battery. Fig.10 The figure is a graph showing the cycle performance test results of the Se-CNT positive electrode and the Se-CNT+SrLNO positive electrode provided in Example 4 of the present invention for aluminum-selenium batteries. It can be seen that the capacity of the Se-CNT+SrLaNiO3 positive electrode is significantly increased (1082mAh g -1 ), so the perovskite compound SrLaNiO3 electrocatalyst can significantly improve the discharge capacity and cycle performance of aluminum-selenium batteries.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A metal-sulfur / selenium battery, characterized in that: include: A positive electrode, a negative electrode, a separator and an electrolyte; the active material of the positive electrode is at least one of sulfur, selenium and sulfur-selenium compounds, and the negative electrode is a metal negative electrode; the positive electrode and / or the separator are loaded with a targeted electrocatalyst, and the targeted electrocatalyst is one or more of metal sulfides, metal nitrides, Prussian blue and its analogs and perovskite compounds.

2. The metal-sulfur / selenium battery according to claim 1, characterized in that: The metal sulfide is one or more of MoS2, WS2, SnS and Bi2S3; the metal nitride is TiN and / or Ni3N.

3. The metal-sulfur / selenium battery according to claim 1, characterized in that: The active material of the positive electrode is a supported active material, including a porous carrier and one of sulfur, selenium and a sulfur-selenium compound supported on the porous carrier.

4. The metal-sulfur / selenium battery according to claim 1, characterized in that: The metal negative electrode is one of lithium, sodium, potassium, magnesium and aluminum.

5. The metal-sulfur / selenium battery according to claim 1, characterized in that: The electrolyte is a carbonate-based electrolyte, an ether-based electrolyte or an ionic liquid.

6. The metal-sulfur / selenium battery according to claim 1, characterized in that: The diaphragm is a glass fiber membrane.

7. The metal-sulfur / selenium battery according to claim 1, characterized in that: The positive electrode loaded with the targeted electrocatalyst is prepared by mixing a positive electrode active material, a targeted electrocatalyst, a conductive agent, a binder and a solvent.

8. The metal-sulfur / selenium battery according to claim 1, characterized in that: The diaphragm loaded with the targeted electrocatalyst is prepared according to the following steps: mixing a targeted electrocatalyst, a conductive agent, a binder and a solvent to obtain a slurry; The slurry is coated on the surface of the diaphragm and dried to obtain a diaphragm modified with a targeted electrocatalyst.

9. The metal-sulfur / selenium battery according to claim 8, characterized in that: The mass ratio of the targeted electrocatalyst, the conductive agent and the binder is (5-10):(0.5-5):

1.

10. The metal-sulfur / selenium battery according to claim 8, characterized in that: The coating dry thickness of the slurry is 50 to 500 μm.